USING INEQUALITIES IN SOLVING TRIGONOMETRIC EQUATIONS AND SYSTEMS OF EQUATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
We are looking at an inequality which represents the assertion that the square of an arbitrary real number will not be negative. To use this statement effectively, we apply it to subtraction. Where and are real numbers.